The effectiveness of e-advertisement towards customer purchase intention: Malaysian perspective - Nikhashemi, Seyed Rajab; Paim, Laily; Fard, Saeideh Sharifi (International Organization of Scientific Research, 2013)
The primary objective of this study was to examine the effectiveness of E-advertisement on customer purchase intention. Beside, this study examined the effect of mediating and moderating demography factors on customer purchase intention in Malaysia. Data from 570 respondents with previous experience on online purchasing products and services were collected. To do so, SPSS 19 was applied to analyze the collected data. Our findings revealed that service quality, social network and brand recognition can highly influence customers’ perception toward web-based advertisement. Consequently, consumers who are more optimistic in web-based advertisement (E-advertisement) have most likely higher intention to online purchase. In other words, the effectiveness of E-advertisement is undoubtedly highlighted in this study. Besides, the results of this study showed that the demography factors cannot mediate the customer perception toward advertisement nor the effectiveness of E-advertisement toward customer purchase intention. On the basis of our results, companies must stress the intrinsic attributes of online advertisement to attract highly-involved consumers and must present a benevolent corporate image for consumers.